The Spanish Influenza among Norwegian ethnic minorities 1918 - 1919 - Svenn-Erik Mamelund (University of Oslo, Department of Economics, 2001)
There are few previous studies that have applied multivariate methods to analyse Spanish Influenza mortality, and for the very first time, Spanish Flu morbidity and case fatality rates are analysed. Previous studies have reported that indigenous populations were the prime victims of Spanish Influenza. The explanations put forward in those studies were not convincing, however, as no controls were made for possibly confounding factors. This paper documents for the first time that areas with high shares of an indigenous population, the Norwegian Sami, have high Spanish Influenza mortality and lethality, net of such confounding factors as wealth, crowding, height, occupational structure, settlement patterns and diffusion. The cause is probably a lack of inherited and acquired immunity against influenza among the Sami. Another ethnic Norwegian minority, Kven (Finnish immigrants and their descendants), however, did not differ significantly from the Spanish Influenza mortality and lethality of the Norwegian majority population.
Keywords: 330; Krankheit; Sterblichkeit; Ethnische Gruppe; Norwegen